Japanese territorial dispute about the Soviet northern provinces )South Kuril Islands until the end of the Cold War( Historical Study (Journal of the College of Education for Women, 2019)
The imposition of (state) policy on the South Kuril Islands.In the Pacific was a subjectof borders dispute between Japan and Soviet Union which appeared clearly afterthe secondGreat War and during the cold war. Despite the end of the Cold War and the collapse of theSoviet Union in 1991, this conflict has continued, thus both countries had to made a historicand legitimate claims to demand the rights of sovereignty and ownership of four islandsoccupied by the Soviet Union after World War II under the international conventions andtreaties, but these claims are proven failures through the continuation of the regional conflict.